Alkaline secondary electrochemical generator using zinc as the anode

JP7651273B2Active Publication Date: 2025-03-26サナジー
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020132735
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2020-08-05
Publication Date
2025-03-26
Estimated Expiration
2040-08-05

Smart Images

  • Figure 0007651273000003
    Figure 0007651273000003
  • Figure 0007651273000004
    Figure 0007651273000004
  • Figure 0007651273000005
    Figure 0007651273000005
Patent Text Reader

Abstract

To provide a secondary electrochemical power generator which has a zinc electrode reduced in densification, and in which formation of zinc dendrite is suppressed.SOLUTION: A secondary electrochemical power generator comprises: a) an electrolyte solution which is an alkaline aqueous solution containing a soluble silicate between 0.15 g / l and 80 g / l in concentration in terms of silica (SiO2) and containing hydroxyl ions of a mole concentration between 4 M and 15 M; and b) a zinc electrode containing a conductive ceramic at least partly consisting of hafnium nitride and / or carbide, and / or magnesium carbide and / or nitride and / or silicide, and / or niobium carbide and / or nitride, and / or titanium carbide and / or nitride and / or silicide, and / or vanadium nitride, and / or, of double carbides and / or nitrides of any two metals selected from among hafnium, magnesium, niobium, titanium and vanadium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of alkaline electrochemical generators, and more particularly to the field of storage batteries.

[0002] The present invention relates to secondary generators with zinc anodes, particularly nickel-zinc, zinc-manganese dioxide, silver-zinc, zinc-air, etc., and fully or partially dissolved cathodes, such as zinc-iodine, zinc-bromine, zinc-hexacyanoferrate, zinc-manganese oxide, etc., with the aim of obtaining a large number of cycles from the zinc electrodes.

[0003] <State of the art> Zinc's energy properties (820 Ah / kg, 5845 Ah / l), electronegativity (1.65 V), low cost and ease of recycling make it particularly interesting as an anode material for electrochemical generators: the theoretical mass energies of nickel-zinc and zinc-air combinations are 334 Wh / kg and 1.320 Wh / kg, respectively. In practice, the mass energies of nickel-zinc accumulators can reach 80 Wh / kg in prismatic form, two to three times that of lead-acid batteries.

[0004] However, although zinc is used in large quantities in alkaline and Leclanche® batteries, it is limited to a few use cycles and is not used in industrial type alkaline batteries, except for silver-zinc batteries used primarily in military applications, and more recently in industrial primary nickel-zinc batteries.

[0005] Zinc dissolves in alkaline media in the form of zincates, and when a zinc-negative battery is charged, dendrites readily form which cause short circuits between electrodes of opposite polarity. Furthermore, the area of ​​the negative electrode on which zinc is deposited varies during charge and discharge cycles, leading to the observed densification phenomenon, which reduces the porosity of the electrode and, consequently, its ability to operate at current densities sufficient for the battery to be of practical use.

[0006] Other factors are a disadvantage of zinc negative electrodes, such as the precipitation of zinc oxide which forms a film that reduces and passivates the active surface of the electrode. Numerous studies have been carried out to understand the mechanisms of zinc precipitation and dissolution in alkaline environments, and numerous patents have been filed proposing different solutions: The use of additives added to the electrolyte or included in the anode active material to reduce the solubility of the zincate is an important subject of the patent; · A mechanical process is also described that allows to circulate the electrolyte alone or the zinc electrodes dispersed in the electrolyte in order to avoid the growth of dendrites by depositing the zinc uniformly; Using pulsed currents, with or without polarity reversal, it is possible to at least partially dissolve the dendrites. Finally, the use of separators that limit or inhibit the diffusion of zincate ions from the negative electrode to the positive electrode: these are for example multi-layer microporous separators or exchange membranes.

[0007] These various techniques can be used alone or in combination, but they are only part of the solution and in some cases lead to higher internal resistance, higher battery costs or more complex implementation. On the other hand, some advocate the addition of lead or cadmium to the negative active material, which is rarely accepted due to its obvious polluting properties.

[0008] Progress has been made by adding additives to potassium hydroxide-based electrolytes, such as small cylindrical nickel-zinc (NiZn) batteries available on the market, but the number of cycles obtained from them does not meet the needs of industrial battery use, which must ensure at least 1,000 deep charge and discharge cycles, which corresponds to more than 80% of the discharge depth.

[0009] A surprising advance has been made by adding a conductive ceramic, preferably titanium nitride (TiN), to the zinc electrode. The innovation described in patent FR 2 788 887 (SCPS) of 27 January 1999 has allowed over 1000 cycles at a discharge depth of 80%, as shown in figure 3 cell 1. The loss of capacity of NiZn accumulators during cycling is mainly correlated on the one hand to a local redistribution and densification of the active material, and on the other hand to the drying and resulting passivation of the zinc electrode.

[0010] The object of the present invention is to provide a new solution to the limited ability of zinc electrodes containing conductive ceramics to provide a large number of cycles by modifying the conditions for oxygen recombination at the zinc surface, i.e., by significantly delaying the passivation of zinc at the anode surface and the onset of generator dryout, while suppressing dendrite formation and maintaining reduced zinc redistribution and densification.

[0011] To this end, the authors of the present invention have shown in a very remarkable way that, contrary to the previously mentioned observations, it is possible, by adding silicates to the alkaline electrolyte, when applied to a generator consisting of such a negative electrode, to significantly reduce the passivation phenomenon of the zinc electrode and the dryout of the generator, and, as a consequence, to increase the cycling life of the system. When examining the current state of the art for zinc anode systems, several patents and studies mention the use of silicates, which show that the addition of silicates produces very different results when the electrolyte is used in small, non-mobile amounts compared to large amounts and / or when there is mobility / circulation within the generator.

[0012] The addition of silicates has been known for quite some time, as evidenced by Thomas Edison's U.S. Pat. No. 858,862, dated July 2, 1907, for the "Lalande System (ZnCuO)", which describes the increased solubility of zinc in electrolytes containing silicates.

[0013] US Patent 3 466 195 A (ESB Inc.), issued on September 9, 1969, mentions the increase in initial capacity and the stability of capacity during storage or calendar life of primary ZnAgO or ZnMnO2 systems when a relatively small amount of silicate, 0.05%, is added to the electrolyte or the positive electrode. It is pointed out by the authors of this patent that silicates have the disadvantage of increasing impedance, and as a result, the amount of silicate in the electrolyte should be kept to the minimum amount necessary to induce the desired improvement. The patent also reports the adverse effect of adding 3% silicate.

[0014] Marshall et al. (Surface technology 5 (1977) 149 - 163) investigated the effect of potassium silicate on the dissolution kinetics of polycrystalline zinc in aqueous potassium hydroxide. Their study provided evidence supporting the conclusion that potassium silicate strongly adsorbs to metallic zinc at near-dissolution potentials. The results showed that OH - "The adsorbed silicate layer also affects the movement of ionic species in the immediate vicinity of the electrode surface. The amount of charge required to cause passivation is then reduced, indicating that silicates promote the passivation of zinc."

[0015] Furthermore, patent EP 1 819 002 A2 dated August 15, 2007 (Powergenix Systems Inc.) states that silicates may limit the solubility of zinc. Patent CN 103794824B B (Hunan science and technology res and dev) dated January 20, 2016 describes the preparation of an electrolyte gel of 5.5-6.5 mol / l KOH, characterized by the addition of silicate in a mass ratio of 0.3-0.5:1, to solve the problem of nickel-zinc battery cycling life. It is also mentioned that this gel reduces the formation of dendrites and dissolution of zinc electrode plates, the latter being consistent with the work of Marshall et al. The addition of silicate is through lithium magnesium silicate or magnesium aluminum silicate, forming a gel characterized by silicate particles of 10-200 nm. However, this is an electrolyte in which solid particles mainly composed of silicate are partially dissolved, so the silicate concentration is low and non-specific.

[0016] Patent FR 2 630 862 (Sorapec SA) published on 3 November 1989 mentions the addition of 1% to 5% silicate to an 8M KOH electrolyte. In a rich electrolyte and in the oxidized state (complete expulsion of zinc), zinc is present in the electrolyte mostly in the form of zincate.

[0017] The beneficial effect of silicates in certain energy storage applications is the phenomenon of greater dissolution of zinc in the form of zincates, which is the case in the abovementioned patent EN 2 630 862, but also in the zinc-air circulation systems described below. In particular, they are used in zinc-air systems with electrolyte circulation or in zinc-air systems with zinc electrode circulation, dispersed in the electrolyte, where it is necessary to increase the amount of zinc dissolved in the alkaline electrolyte, thereby increasing the mass and volumetric energy of the system.

[0018] In fact, A. Gordon Briggs et al. (J. Chem. Soc., Faraday Trans. 2, 1974, 70) have shown that the addition of potassium silicate at a rate of 0.15 mol / l (corresponding to 9 g / l of silica) makes it possible to dissolve 30% more zinc by electrochemical means in a 10 mol / l potash solution than without the addition of silicate, and have also observed that the stability over time of supersaturated solutions (i.e., the absence of precipitation of zinc oxide) is much greater in the presence of silicate.

[0019] PC Foller (J. Appl.Electrochem.16, 1986, 527) describes a zinc-air system with zinc-dispersed electrodes. He uses 25 g / l to 28 g / l of silica in a 12 mol / l potassium carbonate solution. In the presence of silicate, the discharge time of zinc for the same amount of electrolyte doubles, which has the effect of further increasing the solubility of zinc. Interestingly, this same figure of doubling was already reported by Thomas Edison in 1907. Solutions without silicate show a white precipitate of zinc oxide, while those with silicate have a dark color, which the author states is related to the formation of quasi-colloids. At a silica content of 30 g / l, the effect of silicate becomes negative, since the viscosity increases strongly and the silica precipitate passivates the zinc surface, reducing the discharge rate.

[0020] The same electrolyte composition is also used in a zinc-air battery having a bed of zinc particles in US Patent 5,006,424, April 9, 1991 (University of California). Similarly, patent FR2 214 977 (Shell Int Reaction) dated August 19, 1974, proposes the addition of silicate ions to the electrolyte solution to increase the amount of zincate ions that can be dissolved in the caustic electrolyte solution to between 5 and 7 mol / l before zinc oxide begins to precipitate. The patent claims 2 to 4.75 mol / l KOH and 9 to 36 ion-grams / l or 5.86 to 23.5 g / l SiO2 as the electrolyte. The authors note that this electrolyte limits passivation of the zinc electrode in primary systems. In secondary batteries, especially those with microporous electrodes, it is proposed to confine zinc oxide in the pores of the electrode, thereby resisting dendrite growth and shape changes during charging and improving life. In systems using metallic zinc as the electrode in the form of a suspension in the electrolyte, passivation is delayed or inhibited. It is stated that concentrations of silicate ions above 23 ion-gram / l or SiO2 above 15 g / l do not provide any beneficial effect.

[0021] US Patent 4,147,839 (Diamond Shamrock Corp.), issued on April 3, 1979, claims the use of a 45% KOH electrolyte (equivalent to 37 g / l SiO2) containing 54 g / l potassium silicate, characterized by a ratio of K2O to SiO2 of 1:2.2, where the field of application is very specific. This US Patent 4,147,839 applies to a zinc anode formed by a layer of active metal suspended in electrolyte and a current collector, the principle being to completely dissolve all reaction products during discharge and to reverse the reaction during charging. The advantage of silicates is that they increase the solubility of the reaction products, as also explored in patent FR 2 214 977.

[0022] Finally, the effect of silicates on zinc corrosion has been studied by JY Huot (J. Appl. Electrochem. 22, 1992, 443), who showed that silicates at a rate of 2 g / l retard the corrosion of zinc dust in alkaline media, but that this effect is reduced when zincate is present in the solution. Besides this study by J.Y. Huot on the reduction of zinc corrosion in alkaline environments, all the analyzed literature on the use of silicates shows that the action of silicates is aimed at increasing the solubility of zinc, but has a negative effect due to increased passivation, especially in the case of high silicate concentrations.

[0023] Increased zinc solubility is logically required in systems having a circulating electrolyte or a zinc electrode dispersed in the circulating electrolyte. However, for any secondary generator with a more or less limited electrolyte volume and a large negative electrode, the use of silicates does not seem to be logical. In fact, in such a configuration, the dissolution of zinc during recharging is significant, and during successive charging, the redistribution of zinc between and within the negative electrodes and the formation of compacted zones within the negative electrodes increase. Thus, the effective capacity of the negative electrodes gradually decreases, and the imbalance of the charge state of the negative electrodes also accelerates.

[0024] These problems (especially with nickel-zinc batteries) were highlighted by the work of ZP Arkhangel'skaya et al. (Russ. J. Appl. Chem. 70, n°1 1997, 68). The goal pursued in these generator configurations, in contrast, is to reduce the solubility of zinc in order to limit zinc redistribution during charging, as argued, for example, in U.S. patent application Ser. No. 5,556,720 published Sep. 17, 1996 (Charkey).

[0025] An analysis of current literature, patents and studies on alkaline batteries in which silicates are used reveals that they exploit the ability of silicates to increase the solubility of zinc in alkaline media, and none of these documents mention or pursue the improvement of the stability and cycling life of the battery that results from the combined action of a conductive ceramic, preferably titanium nitride, to limit the drying out of the battery and the passivation of the zinc electrode. Summary of the Invention [Problem to be solved by the invention]

[0026] The aim of the present invention is to find a way to prevent dryout in batteries and to prevent densification of the zinc electrodes. To this end, various parameters that affect the stability of the zinc electrodes during charging have been studied.

[0027] Two specific parameters were found to have a beneficial effect: the addition of specific conductive ceramics (especially TiN) to the zinc anode, and the addition of silicates to the electrolyte (see Fig. 3 - cells 1 and 2, respectively). Adding these components separately can give interesting results, but the addition of ceramics, as described in patent FR 2 788 887, is significantly more advantageous than adding silicates alone to the electrolyte. These two components, conductive ceramics and silicates, respectively, inhibit the formation of zinc dendrites and reduce the densification of the zinc electrode. The final observed capacity loss is correlated with different mechanisms, the dryout of the conductive ceramic accumulator, and the passivation of the zinc electrode against the silicates. The amount of silicate added here is 45 g / l of SiO2, much higher than the 30 g / l reported by PC Foller.

[0028] The experimental studies carried out have demonstrated that the combined use of these two components clearly enhances the benefits obtained from their independent action. The mechanism behind this result is also novel, as it correlates with an improvement in the recombination of oxygen on the conductive ceramic, which is not limited by the passivation of the zinc electrode. This means that there is a double constraint for each component used in isolation, on the one hand, due to its negative impact and, on the other hand, due to the limitation of its positive action. [Means for solving the problem]

[0029] The present invention therefore relates to a rechargeable alkaline electrochemical generator with a zinc anode comprising a conductive ceramic, the aqueous alkaline electrolyte of which has a hydroxide ion molar concentration of 4M to 15M and contains silicate in an equivalent silica (SiO2) concentration of about 0.15 g / l to 80 g / l.

[0030] More specifically, the present invention relates to an electrochemical generator according to the following item: 1. A secondary electrochemical generator with zinc electrodes, characterized in that it comprises: a) an electrolyte solution containing a soluble silicate having a silica (SiO2) concentration of 0.15 g / l to 80 g / l and a molar concentration of 4 M to 15 M hydroxide ions; and b) at least in part, Hafnium nitride and / or carbide and / or magnesium carbide and / or nitride and / or silicide and / or niobium carbide and / or nitride and / or titanium carbide and / or nitride and / or silicide and / or vanadium nitride and / or a zinc electrode comprising a conductive ceramic consisting of a nitride of any two metals selected from hafnium carbide and / or dinitride, magnesium, niobium, titanium and vanadium.

[0031] The advantageous properties of the electrochemical generator of item 1 above are shown in items 2 to 8 below: 2. The electrochemical generator of claim 1, wherein the conductive ceramic contained in the zinc electrode comprises titanium nitride.

[0032] 3. The secondary electrochemical generator according to claim 1 or 2, wherein the molar concentration of the alkaline solution is 7 to 13 M.

[0033] 4. The secondary electrochemical generator according to any one of items 1 to 3, wherein the silicate concentration in the electrolyte is 20 g / l to 60 g / l in terms of silica.

[0034] 5. A secondary electrochemical generator according to any one of claims 1 to 4, wherein the alkalinity of the electrolyte is provided by hydroxides of lithium, sodium or potassium, either alone or in admixture.

[0035] 6. A secondary electrochemical generator according to any one of claims 1 to 5, wherein the silicates are derived from silica, fumed silica, silica fume, potassium or sodium silicate, potassium and sodium disilicate, sodium and potassium metasilicates, potassium trisilicate and sodium orthosilicate, provided alone or as a mixture.

[0036] 7. The secondary electrochemical generator according to any one of items 1 to 6, wherein the electrolyte further contains a zincate.

[0037] 8. A secondary electrochemical generator according to any one of claims 1 to 7, wherein the electrolyte further comprises a borate, a phosphate and / or a fluoride. Effect of the Invention

[0038] Other characteristics and advantages of the invention will now be explained in detail in the following description, which refers to the attached schematic representation of the drawings, in which: [Brief description of the drawings]

[0039] [Figure 1] : Charge and discharge voltage of a 4.6Ah NiZn cell as a percentage of the nominal capacity C=4.6Ah of cell A and cell B; [Diagram 2] : Voltage and pressure of 3Ah NiZn cells C and D with and without silicate during three training cycles; [Diagram 3] : Capacity graph measured on discharge of NiZn 8Ah cell during cycling (8A charge, 8A discharge, 1V discharge, 100% discharge depth in 1h): anode with TiN and electrolyte without silicate, 2: anode with no TiN and electrolyte with silicate, 3: anode with TiO2 and electrolyte with silicate, 4: anode with TiN and electrolyte with silicate, [Figure 4] Cumulative mass loss during cycling of the NiZn 8 Ah cell in Fig. 3. 1: anode with TiN and electrolyte without silicate, 2: anode without TiN and electrolyte with silicate, 3: anode with TiO2 and electrolyte with silicate, 4: anode with TiN and electrolyte with silicate, [Diagram 5] : Graph of capacity measured on discharge of NiZn 8 Ah cell during cycling (charge 8 A for 1 h, discharge 8 A, 1 V, 100% discharge depth), 5: Anode without TiN and electrolyte with silicate, 6: Anode with TiN and electrolyte without silicate, 7: Anode with TiN and electrolyte with silicate, [Figure 6] Cumulative mass loss during cycling of the NiZn 8Ah cell in Figure 5. 5: anode without TiN and electrolyte with silicate, 6: anode with TiN and electrolyte without silicate, 7: anode with TiN and electrolyte with silicate; and [Figure 7] : Capacity graph measured on discharging a NiZn 8Ah cell during cycling (8A charge, 8A discharge, 1V discharge in 1h, 100% discharge depth). 8: Anode with TiN and electrolyte without silicate, 9: Anode with TiN and electrolyte with 0.45M silicate, 10: Anode with TiN and electrolyte with 0.85M silicate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] <Detailed Description of the Invention> The zinc negative electrode storage battery of the present invention is manufactured according to methods known to those skilled in the art. The electrode is a plate-shaped electrode consisting of a current collector and an active material. The active material may incorporate compounds that do not participate in the electrochemical reaction, but provide, for example, the function of electronic conduction or mechanical bonding between the active material and the current collector, or the function of retaining the product of the electrochemical reaction.

[0041] In the case of zinc negative electrodes, besides polymers such as PTFE, polyethylene glycol, polyvinyl alcohol, styrene butadiene rubber, carboxymethyl cellulose, etc., which act as binders for the electrode components, calcium hydroxide can be used to limit the formation of soluble zincates, or conductive ceramics can be used, as described in patent FR 2 788 887.

[0042] The separator separates the negative and positive compartments and may be a felt, a porous membrane or an ion exchange membrane; the felt and porous membrane may be combined. The zinc negative electrode storage battery of the present invention may have a cell configuration of a prismatic type, a cylindrical type, or a filter press type, so long as the battery is of a bipolar type, depending on the method of manufacture.

[0043] The invention is particularly, but not exclusively, applicable to the manufacture of nickel-zinc accumulator batteries designed according to the main characteristics described below. According to a preferred manufacturing method, a nickel-zinc storage battery is produced by combining a plasticized nickel electrode with a zinc electrode that also contains an organic binder.

[0044] 1) Nickel electrodes Nickel electrodes can be advantageously realised by using nickel metal foams with very fine pores. Some of these foams are even explicitly labelled as "battery grade". Suppliers of such foams include, for example, Sumitomo Electric of Japan and Corun of China. The thickness of the foam is chosen depending on the desired surface capacity of the nickel electrode: typically between 1.2 and 2 mm, but it can be layered to precisely adjust the thickness to the desired surface capacity.

[0045] The active material preferably consists of nickel hydroxide with coprecipitates of zinc and cobalt. The particles are preferably spherical or spheroidal in shape to increase the volumetric capacity. They may be coated with cobalt oxide and hydroxide which are converted to conductive cobalt oxyhydroxide during formation of the storage battery (Oshitani et al. J. Electrochem. Soc. 1989 136, 6, 1590).

[0046] Additionally, conductive additives (fibers, metal powders) can be added to the nickel hydroxide powder. The paste is prepared by mixing the above ingredients with exchanged water to which carboxymethyl cellulose has been added. At this stage of manufacture, a polymeric binder such as PTFE may be added in the form of a suspension, or later, after the manifold, especially nickel foam, is dipped into the suspension and filled or coated with the active paste.

[0047] Filling of the nickel foam is done on a laboratory scale using a doctor blade that penetrates the paste into the thickness of the substrate, and on an industrial scale by injecting the paste into the foam under pressure. After drying, the electrode is compressed to ensure cohesion between the current collector, active material and additives, and cut to the desired size.

[0048] 2) Zinc electrode The current collector for the zinc electrode can take the form of a perforated metal strip, woven wire cloth, expanded metal strip, metal foam, etc. Copper may be preferred for its electrical conductivity, but it must be covered with a protective metal such as zinc, tin, or an alloy thereof.

[0049] The zinc electrode of the present invention is manufactured by first preparing a paste of zinc oxide and various additives: -Electronic conductors: metallic zinc, carbon, copper, conductive ceramics... in powder or filament form -Corrosion inhibitors: indium, bismuth, etc. - Compounds that react with zincate: calcium hydroxide, barium hydroxide, etc. The liquid phase is deionized water or alcohol, to which carboxymethylcellulose is added as a binder and thickener. Other binders, such as those described in patent EP 1 715 536, can be added.

[0050] Depending on the technique chosen, it is possible to prepare a high viscosity paste that can be applied to both sides of the metal support to form a "sandwich" structure, or a medium viscosity paste can be prepared and the current collector can be removed by dipping it and using a doctor blade to remove the excess paste to adjust the thickness of the electrode, followed by drying. Finally, it is also possible to use the dry powder mixed with a binder and compress it onto a metal support to form the electrode.

[0051] 3) Electrolyte The electrolyte to which the silicate is added is preferably a concentrated alkaline solution having a molarity of hydroxide ions between 4 and 12 M (4 to 12 mol / l). Alkalinity is provided by the hydroxides of potassium, sodium and lithium, either alone or in mixtures. The amount of silicate added to the electrolyte is between 0.15 and 80 g / l, preferably between 20 and 60 g / l, expressed as mass of silica per liter. The electrolyte may also contain zincates in various proportions.

[0052] The silicates are provided in particular by silica, fumed silica, silica fume, or potassium and sodium silicates, such as potassium and sodium disilicate, potassium and sodium metasilicate, potassium trisilicate, sodium orthosilicate, etc. These silicates can be used individually or in mixtures. The electrolyte may also contain borates, phosphates, and fluorides taken alone or in mixtures, as described, for example, in US Pat. No. 5,215,836.

[0053] (Oxygen recombination process) To explain the approach taken to arrive at the present invention, we first describe an analysis of mass loss and oxygen recombination in NiZn cells.

[0054] The charging of the nickel electrode is characterized by the occurrence of some parasitic oxygen evolution reactions before the nickel electrode reaches full charge. In order to prevent the battery drying out due to the oxygen in the battery being exhausted through the sealing valve, it is desirable to recombine the oxygen in the battery to prevent the capacity loss. The recombination of oxygen on the surface of the zinc electrode can be achieved in two ways: (1) Chemical oxidation represented by the reaction 2Zn + O2 + 2H2O ⇒ 2Zn(OH)2 (2) Catalytic reduction of conductive zones such as metallic zinc and titanium nitride, as represented by the following reaction: O2+2H2O+4 e- ⇒ 4OH- and / or O2 + H2O + 2e- ⇒ HO2 - +OH - (Charging only)

[0055] For these two reaction mechanisms to be efficient, a three-phase solid-liquid-gas contact point is required, the gas being oxygen at the surface of the zinc electrode. Therefore, the access of oxygen to the surface of the zinc electrode is the determining parameter to ensure recombination.

[0056] The access of oxygen to the surface of the zinc anode is limited by various barriers. They are classified from most to least restrictive and are characterized by different physical states: the liquid phase is the electrolyte at this surface, the solid phase is the porous separator placed on the surface of the zinc electrode, and the gas phase is composed of hydrogen evolved at the surface of said anode. This evolution of hydrogen represents an indirect effect and obstacle by increasing the amount of electrolyte at the interface when the electrolyte level is low.

[0057] Two NiZn cells A and B with a nominal capacity of 4.6 Ah are fabricated using identical electrodes and electrolyte composition according to the general description above. The electrolyte used is a concentrated alkaline solution of KOH with no added silicate and a molarity of 10M hydroxide ions. Titanium nitride is homogeneously introduced into the active mass of the zinc anode for cell A, and the same amount of TiN is preferentially deposited on the surface of the zinc electrode for cell B. The cells are hermetically sealed and equipped with a valve that opens at pressures above 2 bar.

[0058] Cells A and B were charged at C / 10 with a state of charge of 100% to 180% and discharged at C / 5 with a cutoff voltage of 1.2. Table 1 and Figure 1 show an example of a 180% state of charge. The mass loss (DM) of the cell was measured, and the gas recombination rate (TRG) was calculated by converting the ampere-hour difference between charge and discharge into the potential mass loss of water (Table 1 below).

[0059] For cell A, the gas recombination rate decreases with increasing state of charge. This behavior was not verified for cell B, which is characterized by a two-fold lower overall mass loss and an increased gas recombination rate at 180% state of charge compared to the one calculated at 140%. This result corresponds to an increase in the catalytic activity of TiN towards oxygen by step (2), which we attempt to demonstrate here by showing that the phenomenon is accentuated when TiN is present primarily at the surface of the anode and in greater amounts there than when the same amount overall is distributed throughout the anode volume.

[0060] The present invention aims to enhance the catalytic activity of TiN towards oxygen recombination in order to eliminate the anode passivation mechanism and drying out of zinc anode cells.

[0061] [Table 1]

[0062] Seeking to define a new embodiment likely to eliminate the mechanism of passivation of the negative electrode and drying out of the generator according to the invention, the authors carried out identical comparative experiments on 3 Ah NiZn cells C and D, realized according to the general description already given - except for the electrolyte - whose zinc negative electrodes contained TiN.

[0063] The electrolyte used is a concentrated aqueous alkaline solution with 10M moles of hydroxide ions in cell C. The electrolyte is modified for cell D by adding 0.82M silicate provided by silica.

[0064] The internal pressure of the cell is measured by a 0-10 bar pressure sensor, and the cell is fitted with a safety valve that opens at pressures above approximately 0.85 bar. The initial formation of the two cells was performed by charging at C / 10 for 12 hours and discharging at C / 5 to a discharge cut-off voltage of 1.2V for 3 cycles.

[0065] The voltages and pressures for cells C and D are given in FIG. 2 for three cycles. The pressure measurement of cell D containing the silicate electrolyte is characterized by the absence of valve opening. Conversely, the internal pressure of cell C without the addition of silicate to the electrolyte is characterized by an open valve, especially in the region at the beginning of the charge, which preferably includes hydrogen evolution at the zinc electrode.

[0066] These results indicate that the presence of silicate in the electrolyte suppresses hydrogen production and improves oxygen recombination. Without silicate, the low hydrogen overpotential of TiN limits hydrogen evolution in the center of the porous anode. The electrolyte contained in the pores of the zinc electrode is partially forced towards the electrode interface. The electrolyte film at the electrode interface then increases in thickness, limiting oxygen access to the catalytic recombination zone of TiN. This leads to preferential recombination on the Zn metal via a chemical recombination step (1), which leads to the phenomenon of drying and passivation by the formation of Zn(OH)2, and a progressive loss of capacity.

[0067] With silicates, pressure measurements show that the amount of hydrogen evolution is significantly reduced. Analysis of this phenomenon makes it possible to consider a hypothesis, which is published here without limiting the scope of the invention. According to it, by depositing on the surface of the zinc electrode, silicates separate the TiN and the Zn metal, forming an insulating interface between the two, which makes it possible to reduce the hydrogen evolution. In this way, the access of oxygen to the TiN is improved, allowing the recombination to take place preferentially according to the catalytic step (2), which does not lead to the phenomena of drying and passivation.

[0068] To trace and illustrate the operation and definition of the present invention, NiZn cells 1, 2, 3 and 4 with a nominal capacity of 8 Ah have been manufactured in an identical manner according to the general description provided above. The cells are fitted with a 0.2 bar low pressure valve. The nickel hydroxide used in the positive electrodes of these cells 1-4 contains 5% cobalt. The electrolyte used is a concentrated alkaline aqueous solution with a hydroxide ion mole count of 10M for cell 1. The electrolyte is modified for cells 2, 3 and 4 by adding silicate. The parameters that distinguish cells 1-4 are summarized in Table 2 below.

[0069] Characteristics of NiZn storage battery: nominal capacity 8Ah, cycle charge 8A 1h, 100% discharge 8A 1V. [Table 2] In cell 3, the titanium nitride is replaced with a titanium oxide compound. The battery was cycled at a constant current of 8A, equivalent to the C system, and discharge was terminated when the voltage reached 1V after 1 hour of charging.

[0070] A comparison of the discharge capacity and cumulative mass loss of batteries 1 to 4 according to the number of cycles is shown in FIG. 3 and FIG. 4, respectively. It can be seen that the stability of the battery capacity is continuously improved. Addition of silicate alone, batteries 2, 3 (TiO2 does not have the effect of TiN). · TiN only, storage battery 1 ·Addition of TiN and silicates, storage battery4.

[0071] The results are shown in Table 2. It can be seen that 90% of the initial capacity is maintained after 770, 770, 1.120 and 1.380 cycles for cells 2, 3, 1 and 4, respectively. After 90% of the remaining capacity, the capacity of the batteries drops rapidly, except for 4 (TiN, silicate). Battery 4 (TiN and silicate) retains more than 75% of its initial capacity after 1,885 cycles, a 50% improvement over battery 1, which retains 75% of its initial capacity after 1,260 cycles.

[0072] Batteries 2 (silicate without TiN) and 3 (silicate and TiO2) had the highest mass loss, suggesting that insufficient oxygen recombination limits the dryout of the battery. According to PC Foller's paper, when the silica loading exceeds 28-30 g / l, passive silica is deposited on the zinc surface. This deposit reduces the recombination strength of the zinc electrode.

[0073] In the context of the present invention, the authors further show that in alkaline media, complexes formed between silicate and zincate ions, especially in porous zinc anodes, show stability and measure a lower mobility than the smaller zincate ions alone, due to the increased steric effect of the zincate complexed by silicate. The suppression of the mobility of the zincate ions by complexation with silicate ions constitutes a parameter that is likely to contribute to the reduction of zinc redistribution and densification phenomena in the anode.

[0074] The formation of complexes between silicate and zincate ions in alkaline media has been mentioned by several authors, who described it by Michel R. Anseau et al. (Inorg.Chem. 44, 8023-8032, 2005) as reacting in strongly alkaline media (zincates, in 14-15 mol / l potassium hydroxide or sodium hydroxide solutions) with monomeric, dimeric and cyclotrimeric silicates to form very stable compounds.

[0075] The mass loss of batteries 1 and 4 (with TiN) is much lower than that of batteries 2 and 3. It is interesting to note the different progression between these two batteries 1 (with TiN) and 4 (with TiN and silicate). From 0 to 900 cycles, the mass loss of battery 4 increases very slowly and linearly, whereas battery 1 accelerates from cycle 300 onwards. This result is consistent with an improvement in stability associated with a decrease in densification of the zinc electrode, as expected by complexation of the zincate with silicate. Between 900 and 1,260 for battery 1 and between 1,000 and 1,300 for battery 4, there is a sharp increase in mass loss due to the increase in oxygen at the end of charge. For Battery 1, from 1,200 cycles onwards, the mass loss becomes very significant, meaning that the capacity drops rapidly after the cell dries out and the electrodes passivate. Battery 4 shows a peculiar behavior characterized by a moderate overall mass loss beyond 1,300 cycles, where the progression of loss slows again due to effective recombination of oxygen limiting drying and long-term electrode passivation.

[0076] In this way, it can be seen that simply by adding titanium nitride to the negative electrode (battery 1) or silicate to the electrolyte (battery 2), the formation of dendrites is suppressed, the densification of the zinc electrode is suppressed, and a satisfactory response can be obtained in terms of the stability of the zinc electrode. However, the addition of titanium nitride is much more effective than adding silicates to the electrolyte.

[0077] However, it is a very significant improvement in operation that is measured during the simultaneous addition of titanium nitride to the zinc electrode and silicate to the electrolyte (accumulator 4), which corresponds to a significant improvement in the oxygen recombination power at the zinc electrode, eliminating the phenomenon of system dryout and passivation of the zinc electrode. The silicate brings about a previously unknown effect of enhancing the catalytic oxygen reduction power of conductive ceramics such as titanium nitride.

[0078] In the following comparison, NiZn batteries 5, 6 and 7 with a nominal capacity of 8 Ah are manufactured in the same way, following the general description given above. The cell is fitted with a 0.2 bar low pressure valve. The nickel hydroxide used in the positive electrodes of these cells 5-7 contains 8% cobalt. Increasing the amount of cobalt improves the conductivity of the nickel hydroxide, which then charges the nickel electrode more efficiently and reduces oxygen evolution, mitigating accumulated mass loss.

[0079] The electrolyte used is a concentrated alkaline aqueous solution with a hydroxide ion mole number of 10 M in cell 6. The electrolyte is modified in cells 5 and 7 by adding a large amount of silicate. The anode of cell 5 does not contain TiN. The parameters that distinguish cells 5 to 7 are summarized in Table 2 below. Batteries 5 to 7 are cycled at a constant current of 8A, which corresponds to the C system, and are charged for 1 hour, with discharging ending when the voltage reaches 1V.

[0080] A comparison of the discharge capacity and cumulative mass loss of batteries 5 to 7 according to the number of cycles is shown in Figures 5 and 6, respectively. The results are shown in Table 2 below. According to the sequence without TiN and with silicate (accumulator 5), with TiN and without silicate (accumulator 6) and finally with TiN and with silicate (accumulator 7), the stability of the capacity of the accumulators improves with remaining capacity of 90% of the initial capacity after 500, 1,200 and 1,700 cycles respectively. (See Table 2) The number of cycles is lower for accumulator 5 (0.45 M SiO2 or 27 g / l) than for accumulators 2 and 3 (0.75 M SiO2 or 45 g / l), indicating the beneficial effect of the addition of more than 30 g / l of silicate as SiO2. This is in contrast to the current state of the art, which shows a passivation after SiO2 precipitation and also a capacity drop due to an overly viscous electrolyte. (Paper by P.C.Foller).

[0081] At 90% of the initial capacity, battery 7 shows a 42% progress in capacity stabilization compared to battery 6. The progression of mass loss in batteries 6 and 7 is similar to batteries 1 and 4, confirming the peculiarities of the oxygen recombination force in batteries with titanium nitride in the zinc electrodes and silicate added to the electrolyte.

[0082] In the following comparison, NiZn accumulators 8, 9 and 10 with a nominal capacity of 8 Ah are manufactured in the same way, according to the general description given above. The cells are fitted with a 0.2 bar low pressure valve. The nickel hydroxide used in the negative electrodes of cells 8-10 is the same as that in cells 5-7 above. Cells 8-10 have zinc electrodes with titanium nitride. Compared to cells 6 and 7, the preparation of the active material paste for the zinc electrode has been modified according to a procedure that increases the homogeneity of the components of this active material without changing the chemical composition. The electrolyte used is a concentrated alkaline aqueous solution with a hydroxide ion mole count of 10M for cell 8. The electrolyte is modified by the addition of a large amount of silicate, 0.45M and 0.85M for cells 9 and 10, respectively.

[0083] The storage batteries 8 to 10 are cycled at a constant current of 8A, which corresponds to the C system, and charging takes one hour, and discharging is terminated when the voltage reaches 1V. The discharge capacity as a function of the number of cycles performed for batteries 8 to 10 is compared in FIG. The results are also shown in Table 2.

[0084] Battery 8 (with TiN and silicate) only retains 70% of its initial capacity after 1,300 cycles, while battery 9 (with TiN and 0.45M silicate) retains 70% of its initial capacity after 2,640 cycles, an increase of 103%. Battery 10 (with TiN and 0.85M silicate) retains 70% of its initial capacity after 2,680 cycles, an increase of 106% compared to battery 8.

[0085] These various results show that the effect of using titanium nitride as the anode and silicate as the electrolyte is surprising, as it increases the number of cycles by more than 100%. They also reflect, as predicted by the authors of the present invention, a decrease in zinc densification and a change in the shape of the zinc electrode, associated with the formation of zinc-silicate complexes, which limits their average free motion in the electrolyte, including in the negative electrode, and therefore reduces the redistribution of zinc.

[0086] Additionally, the combination of a conductive ceramic such as TiN with a silicate modifies the oxygen recombination strength of the zinc electrode, promoting oxygen recombination according to catalytic step (2) above. The silicates no longer passivate the surface of the zinc electrode, as is observed in the absence of TiN. These phenomena limit the drying out of the battery and significantly improve the cycle life. It is therefore a novel effect observed during the combination of a conductive ceramic such as TiN in a zinc anode and a silicate in the electrolyte that is the subject of the present invention.

[0087] Naturally, and as it significantly achieves the above results, the present invention is not limited to the particular embodiments that have been described for purposes of illustration and demonstration. The present invention is not limited to the embodiments presented, but encompasses all variations thereof.

Claims

1. A secondary electrochemical generator comprising: a) Silica (SiO 2 ) an electrolyte solution which is an alkaline aqueous solution containing a soluble silicate having a converted concentration of 20 g / l to 60 g / l and a molar concentration of 7 M to 13 M hydroxide ions; b) a zinc electrode comprising a conductive ceramic comprising titanium nitride; and c) Nickel electrode.

2. A secondary electrochemical generator as described in claim 1, wherein the alkalinity of the electrolyte is provided by hydroxides of lithium, sodium or potassium taken alone or in mixtures.

3. A secondary electrochemical generator as described in claim 1 or 2, wherein the silicates are obtained from silica, fumed silica, silica fume, potassium or sodium silicate, potassium and sodium disilicate, sodium and potassium metasilicate, potassium trisilicate and sodium orthosilicate, these silicates being provided alone or as a mixture.

4. A secondary electrochemical generator described in any one of claims 1 to 3, wherein the electrolyte further contains zincate.

5. 5. The secondary electrochemical generator of claim 1, wherein the electrolyte further comprises a borate, a phosphate and / or a fluoride.

Citation Information

Patent Citations

  • JP1974104141A

  • Electrode material used in battery half cell

    JP1989265457A

  • Method of charging zinc suspension battery, zinc suspension battery and zinc suspension for battery

    JP1993013110A

  • alkaline battery

    JP1995502375A

  • Alkaline secondary electrochemical generator of zinc positive electrode

    JP2000228198A